Vessel‐On‐A‐Chip Coupled Proteomics Reveal Pressure‐Overload‐Induced Vascular Remodeling - Yanjun Liu; Jianxujie Zheng; Lingyan Zhong; Zengyu Wang; Dan Zhao; Hong Lin; Xiaoxue Zhang; Ke Meng; Xiaoxia Yang; Dongxue Zhang; Ling Lin; Liang Qiao (Advanced Science)
Abstract Hypertension, the leading cause of cardiovascular disease and premature mortality, is characterized by increased vessel stretch and alterations in vascular smooth muscle cells (VSMCs). In this study, a vessel‐on‐a‐chip model is developed to simulate both physiological and pathological stretch conditions alongside a mouse model of hypertension. Proteomics analysis is applied to investigate changes in VSMCs using the vessel‐on‐a‐chip system and compared these findings with data from the mouse model. The results demonstrates that physiological stretch enhances the expression of contractile markers in VSMCs. Additionally, the chip effectively replicates cellular responses to pathological stretch and stress, including the upregulation of ERK signaling, calcium ion transport pathway, integrin signaling pathway, endoplasmic reticulum stress, toll‐like receptor activation, oxidative stress, and synthesis of sphingolipids and ceramides. These findings indicate that the vessel chip successfully mimics in vivo biological events associated with hypertension. The vessel‐on‐a‐chip system holds promise for advancing the study of vessel‐related diseases and facilitating the development of novel hypertension therapeutics.